ACCOUNTING FOR DECISION-MAKING. - Davidson, H. Justin; Trueblood, Robert M. (The Accounting Review, 1961)
The accounting systems of business have traditionally provided much of the financial data and much of the analysis of that data applicable to decision-making purposes. Today, however, there are symptoms of management dissatisfaction with current accounting systems. Accounting for decision-making involves a particular way of viewing the decision-making, or managing process in business. Choice of a best alternative requires criteria against which to judge various possibilities. Choice requires information concerning the various alternatives, information cast in a form consistent with the criteria. It has been assumed that the decisions to he made by an organization must first he specified before an intelligent design of the information flow is possible. Determination of the decisions to be made comes properly before specification of the data which should be supplied. An organization which does not recognize that it has a poor system for routine inventory decisions will suffer reduced profits. Accounting has an obligation to take a significant part in the development of new quantitative information systems. Accounting must divert itself from its preoccupation of the past with fiduciary and stewardship responsibilities.